PROTOTIPE ROBOT PENGANTAR MAKANAN BERBASIS ARDUINO MEGA DENGAN INTERFACE WEB BROWSER - Asep Saefullah; Endang Sunandar; Muhammad Nur Rifai (Universitas Raharja, 2017)
In general, the process of delivering food is still done traditionally, for example food vendors in the cafeteria by way of delivering food orders and bringing food using the hands of food vendors to the buyer's table. Food delivery is traditionally considered ineffective as food vendors have to walk back and forth to deliver food and leave other jobs. For that we need to designed a system of food delivery robot useful for the seller to help deliver food, The prototype design of food delivery robot using Arduino Mega microcontroller, the robot has a place to put food, and able to walk with the DC motor on the wheel. For movement of the robot body direction using a single servo motor and ethernet shield and TP-Link as a communication bridge between Web Browser with Arduino Mega. Web Browser has a function as a user interface that can be used by food vendors to control the robot. The existence of prototype food delivery robot is expected to help the activities of delivering food made by food vendors well so that food vendors can do other more mainstream jobs